Validity of General Movement Assessment Based on Clinical and Home Videos. Issue 1 (January 2020) - Yeh, Kuo-Kuang; Liu, Wen-Yu; Wong, Alice May-Kuen; Lein, Reyin
Abstract : Introduction: The purposes of this study were to develop an instructional leaflet on home video recording for the General Movement Assessment (GMA) and to examine the concurrent and predictive validity of the GMA completed by physical therapists (PTs) and completed by parents. Methods: The GMA and the Alberta Infant Motor Scale (AIMS) were completed by PTs in the clinic. Parents completed the GMA following the instructional leaflet. Results: The content validity of the leaflet was 0.83. The consistency of the GMA results between sources was κ = 0.869. The concurrent validity of the GMA at a corrected age of 3 months was κ = 0.266 (PT) versus 0.525 (parent) using the 10th-percentile cutoffs of the AIMS. The positive likelihood ratio was 26 (PT) versus 25 (parents) at a corrected age of 12 months based on 5th-percentile cutoffs of the AIMS. Conclusions: Home GMA videos are valid for clinical assessment following the instructional leaflet. Abstract : Supplemental Digital Content is Available in the Text.The purposes of this study were to develop an instruction leaflet on home video recording for General Movements Assessment and to examine the concurrent and predictive validity of this assessment completed by physical therapists and completed by parents.